2009
DOI: 10.1097/hjh.0b013e32832c417d
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of colour duplex sonography for the diagnosis of renal artery stenosis

Abstract: ACCmax and AImax provide similar, good diagnostic accuracy in the detection of a haemodynamically significant RAS, even in patients with markedly reduced glomerular filtration rate. Presumably, the lack of superiority of the novel index AImax could be explained by a highly homogenous methodological approach in the present single-centre study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Previous research 13,[15][16][17][18] and our study both show that ACC max is a feasible noninvasive technique for assessing the severity of PAD and renal artery stenosis. In contrast, other duplex parameters are limited to identify the severity of a PAD (particularly at multilevel stenoses).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous research 13,[15][16][17][18] and our study both show that ACC max is a feasible noninvasive technique for assessing the severity of PAD and renal artery stenosis. In contrast, other duplex parameters are limited to identify the severity of a PAD (particularly at multilevel stenoses).…”
Section: Discussionsupporting
confidence: 68%
“…Van Tongeren et al 13 and Buschmann et al 14 showed the accurate diagnostic properties of ACC max , also in diabetic patients. Although ACC max has already been used to detect renal artery stenosis, [15][16][17][18] to our knowledge, it has not been evaluated thoroughly for PAD. We think that if you want to introduce a new parameter to diagnose PAD, you must start from basic principles.…”
mentioning
confidence: 99%
“…Such variables may explain why some authors have not been able to reproduce these results [30,35]. Therefore, these criteria are used only when obvious on spectral traces, when quantifying the stenosis as severe (> 75%), or when identifying a downstream pattern of a stenosis on a segmental or an accessory artery that has been missed [28,36]. Most accrediting organizations recommend the use of a combination of intraand extrarenal parameters, as it results in an overall sensitivity of 89% and specificity of 92% [11,37].…”
Section: Distal Criteria (Indirect Evaluation Of the Stenosis)mentioning
confidence: 99%
“…Renal artery aneurysms were identified in four of 716 (0AE6%) potential kidney donors, all four presenting with lesions suggestive of FMD; furthermore, 12 of 125 (9AE6%) patients with symptomatic renal artery FMD also had renal artery aneurysms [17] and Brussels [18]. [1].…”
Section: Screening For Intracranial Aneurysmsmentioning
confidence: 99%
“…Several studies suggest that echo-Doppler velocimetric indexes, particularly acceleration time, may reliably predict the existence of a significant stenosis [17,18]. However, these studies included only few patients with FMD.…”
Section: Diagnosis Of Significant Stenosismentioning
confidence: 99%